In Situ Construction of Stable Tissue-Directed/Reinforced Bifunctional Separator/Protection Film on Lithium Anode for Lithium-Oxygen Batteries - Xu, Ji-Jing (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.